Increased transpiration is correlated with reduced boron deficiency symptoms in the maize tassel‐less1 mutant. Issue 3 (17th July 2018) - Matthes, Michaela S.; Robil, Janlo M.; Tran, Thu; Kimble, Ashten; McSteen, Paula
Abstract : Loss‐of‐function mutations of the tassel‐less1 (tls1) gene in maize, which is the co‐ortholog of the Arabidopsis boron (B) importer NIP5;1, leads to the loss of reproductive structures (tassels and ears). The tls1 phenotypes can be rescued by B supplementation in the field and in the greenhouse. As the rescue with B supplementation is variable in the field, we investigated additional abiotic factors, potentially causing this variation in controlled greenhouse conditions. We found that the B‐dependent rescue of the tls1 mutant tassel phenotype was enhanced when plants were grown with a mix of high‐pressure sodium and metal halide (MH) lamps. Normal and tls1 plants had a significant increase in transpiration and increased B content in the leaves in the greenhouse with the addition of MH lamps. Our findings imply that B transport to the shoot is enhanced through increased transpiration, which suggests that the xylem transpiration stream provides a significant supply of B in maize.